Interstitial Lung Disease Is a Major Characteristic of Patients Who Test Positive for Anti-PM/Scl Antibody - Ge, Yongpeng; Shu, Xiaoming; He, Linrong; Li, Chunjia; Lu, Xin; Wang, Guochun (Frontiers in Medicine, 2022)
Objective: This study aimed to analyze the clinical features of anti-PM/Scl antibody in Chinese patients. Method: We reviewed the clinical data of anti-PM/Scl antibody positive patients, including their long-term follow-up. Results: A total of 30 patients carried anti-PM/Scl antibodies, 21 (70%) were females, and mean age was 55.4 years, 15 (50%) and 10 (33.3%) patients were positive for anti-PM/Scl-75 and anti-PM/Scl-100, respectively. Fifteen cases (50%) were diagnosed as inflammatory myopathy, including 11 dermatomyositis (DM) and 4 polymyositis (PM). Five (16.7%) patients were diagnosed as overlap syndrome, and only one (3.3%) was diagnosed as systemic sclerosis (SSc). The other 9 (30%) patients were classified as undifferentiated connective tissue disease (UCTD). Twenty-six (86.7%) had interstitial lung disease (ILD) and was the sole manifestation in 8 (26.7%) patients, 15 (58.0%) showed nonspecific interstitial pneumonia (NSIP) based on HRCT or lung biopsy. The majority of patients (95%) with mild and moderate group on basis of pulmonary function tests (PFTs). Compared to the anti-PM/Scl-100 group, the occurrence of clinical characteristics was not significantly different from the anti-PM/Scl-75 group, except the levels of C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) in the anti-PM/Scl-75 antibody-positive group were higher (p < 0.05). All patients with positive Ro-52 antibody had ILD, and were more likely to develop skin rash in group with Ro-52 (p = 0.024). With follow-up of the present cohort, 70.8% improved with treatment, but 16.7% of patients are easy to relapse. Conclusions: The anti-PM/Scl antibody occurred frequently in DM/PM patients, ILD was the major clinical feature, especially in patients combined with Ro-52. Some patients may complicate with ILD alone without extrapulmonary manifestations. Anti-PM/Scl antibodies positive patients were responsive to treatment.